ATERNATIF PREVENTIF KEKERASAN DALAM RUMAH TANGGA PERSPEKTIF AL-QUR’AN DAN SUNNAH - Ubaidillah, M. Burhanuddin; Ashdaf, Tanthowy (ADIDAS: Asosiasi Dosen Syari'ah STAI Darussalam Nganjuk, 2023)
The reality shows that many wives experience domestic violence. From mass media information, both print and electronic media, it is known that domestic violence is a concerning issue. The violence perpetrated by husbands against wives takes various forms and can be broadly categorized into four types: physical violence, psychological violence, sexual violence, and economic violence. Hadith that informs that angels will curse a wife if she refuses to fulfill her husband's sexual needs needs to be understood accurately and should not be interpreted as applicable in any situation. In reality, some husbands force their wives to satisfy their sexual desires during menstruation, postpartum bleeding, or engage in anal sex. There are also cases where sexual relationships are initiated with physical violence, causing wives to feel raped by their own husbands. Some husbands force their wives into prostitution, and many husbands neglect the clothing and food needs of their family members, resulting in their wives and children being abandoned. This article focuses on four types of domestic violence from an Islamic perspective according to the Qur'an and Sunnah. First, physical violence. Second, psychological violence. Third, sexual violence. Fourth, economic violence. The aim is to build an Islamic understanding against domestic violence so that perpetrators can recognize their wrongdoing, provide advocacy for victims of domestic violence, and offer preventive alternatives.